2023
DOI: 10.1002/vetr.3411
|View full text |Cite
|
Sign up to set email alerts
|

Decision making on antimicrobial use: Cat and dog owners’ knowledge and preferences for veterinary communication

Erin Frey,
April Kedrowicz,
Mari‐Wells Hedgpeth

Abstract: BackgroundVeterinarians' understanding of cat and dog owners’ perceptions about antimicrobial use will enhance their ability to communicate with clients to uphold antimicrobial stewardship guidelines.MethodsA total of 571 cat and dog owners were surveyed via an online platform to understand their antimicrobial knowledge and preferences for veterinary communication in antimicrobial use decision making. Data were analysed descriptively and inferentially to determine relationships between variables.ResultsCat and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(118 reference statements)
0
0
0
Order By: Relevance
“…In fact, Stallwood et al (2019) [49] obtained a percentage of cat owners as high as 84% who correctly recognized bacteria as the true microorganism upon which antibiotics act. High percentages were also obtained by Scarborough et al (2021) [41] and Frey et al in 2023 [52]. On the other hand, Taylor and Walter's study from 2022 [53], which focused on Colorado pet owners' perceptions of antimicrobial drug use, reflected comparable poor knowledge on the subject, as approximately 40% of their participants revealed a lack of familiarity with antibiotics' ineffectiveness against viruses.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In fact, Stallwood et al (2019) [49] obtained a percentage of cat owners as high as 84% who correctly recognized bacteria as the true microorganism upon which antibiotics act. High percentages were also obtained by Scarborough et al (2021) [41] and Frey et al in 2023 [52]. On the other hand, Taylor and Walter's study from 2022 [53], which focused on Colorado pet owners' perceptions of antimicrobial drug use, reflected comparable poor knowledge on the subject, as approximately 40% of their participants revealed a lack of familiarity with antibiotics' ineffectiveness against viruses.…”
Section: Discussionmentioning
confidence: 89%
“…Further to this, Stein et al (2021) [ 39 ] revealed that the importance of an antimicrobial for treating people was the lowest priority for dog owners in North America, as compared to the cost and ease of administration. Frey et al (2023) [ 52 ] demonstrated that pet owners’ expectations related to antimicrobial use in their pets vary with their knowledge of antimicrobial usefulness and with the recognition of the implications of antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 99%